Gambaran Pengetahuan Ibu terhadap Resiko Tinggi Kehamilan dengan menggunakan Lembar Balik di BPM Nurhasanah Pontianak - Nurhasanah Nurhasanah; Yetty Yuniarty; Hariati Hariati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
High risk pregnancy is a condition that can affect the condition of the mother and fetus in the pregnancy she is facing (Manuaba, 2012). Pregnant women who experience medical disorders or health problems will be included in the high risk category, so that the need for implementing care during pregnancy becomes greater (Robson and Waugh, 2012). others include miscarriage, obstructed labor, antepartum bleeding, fetal death in the womb (Intra Uterine Fetal Death), poisoning in pregnancy, babies born under term, and low birth weight babies. The impact of high-risk pregnancies can be prevented through regular prenatal care (antenatal care) which aims to keep the mother healthy during pregnancy, childbirth and postpartum as well as ensuring that the baby is born healthy, containing possible pregnancy risks, and optimal management planning. against high-risk pregnancies and reducing maternal and infant morbidity and mortality. Antenatal services can detect and handle high risk cases adequately, provide clean and safe delivery assistance, affordable obstetric/perinatal services and referrals